Optimization of the SDS formation from edible canna starch by beta cyclodextrin - Luong, Hong Nga; Vu, Thi Thu Thuy; Luong, Van Bang; Vu, Hoang Nam; Anh, Ngo Thi Hoai; Khoi, Nguyen Truong; Son, Vu Hong (JST: Engineering And Technology For Sustainable Development, 2025)
Slowly digestible starch is the starch fraction that is digested at a slow rate in the body, meaning it is broken down by the digestive enzyme in human body during 20 to 120 min. after eating. Recently, SDS and RS are widely studied worldwide because of their various positive health effects: releasing glucose at a slow rate, thereby maintaining sufficient blood glucose, glycemic index and insulin levels, reducing the risk of Type II diabetes, etc.. The goal of the research was to identify the optimal conditions for maximizing the production of SDS from edible canna starch by using β-cyclodextrin with four factors examined: water content, β-cyclodextrin content, reaction temperature, and reaction time. When amylose in starch interacts with β-cyclodextrin through their hydrophilic shells, amylose-β-cyclodextrin (amylose-β-CD) and amylose-β-CD-lipid complexes are formed. These complexes exhibit a V-type crystalline structure characterized by low stability. It facilitates an increase in the production of SDS. The results showed that with a water content of 81.3%, β-cyclodextrin content of 3.1%, reaction temperature of 36℃, and reaction time of 1.8 hours, the slow-digesting starch SDS content obtained from edible canna starch up to 44.88%.